We have to solve the equations 1/x=(y-1)/y and 3/x=(2y-1)/y

1/x=(y-1)/y

=> x = y/(y - 1)

Substitute x = y/ (y - 1) in 3/x=(2y-1)/y

=> 3/x=(2y-1)/y

=> 3 /[y/ (y - 1)] = (2y-1)/y

=> 3(y - 1)/y = (2y - 1)/y

=> 3y - 3 = 2y - 1

=> y = 2

x = 2/(2 - 1) = 2

**Therefore we get x = 2 and y = 2**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now